Alpine tectonic movements and salt tectonics of Eastern Ukraine - Sergey Goryainov (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія, 2022)
Within Eastern Ukraine, in the course of previous studies, neotectonic movements were established, caused by both salt tectonics and Attic (post-Miocene - pre-Pliocene) thrust dislocations of northeastern vergence. They are partially displayed in modern relief.